MUSEUM SPECIAL LIBRARIES IN THE REPUBLIC OF SERBIA - SITUATION AND PERSPECTIVE (Heritage, 2022)
The subject of this paper is museum special libraries in institutions for the protection of movable cultural property. The state of museum libraries in Serbia and the importance they have in the development of our culture are presented. The changes that took place in their work were analyzed through the analysis of statistical data and through comparisons with special libraries that are part of different types of organizations.According to the data of the National Library of Serbia, which keeps a register of all libraries in the Republic of Serbia, 50 registered museum libraries have been identified, their work has been analyzed and the state and possibilities of development have been presented. Since special libraries function within the organization of which they are a part, they organize their work following the needs of the founders. On the other hand, they carry out their basic library and information activities following legal norms, and rules of the profession, as well as through cooperation with related libraries. The review and analysis of the work of museum special libraries aims to highlight their needs, examine the possibilities for overcoming certain problems and improve activities in conditions comparable to related libraries that have the same or similar status within the organization in which they are located.
Keywords: museum libraries, museums, libraries, statistics